Low-carbon tourism approach as an alternative form for tourism development: a review for model development - Che Leh, Fauziah; Mohd Isa, Nor Kalsum; Ibrahim, Mohd Hairy; Ibrahim, Mansor; Mohd Yunos, Mohd Yazid; Ibrahim, Johan Afendi (Universiti Putra Malaysia, 2021)
The tourism industry is a major contributor to the gross domestic product of several countries, including Malaysia. However, recent tourism growth has led to increase the industry’s carbon dioxide (CO2). Low-carbon tourism, therefore, needs to be introduced to the sector to help curb global climate change. A comprehensive understanding of low-carbon tourism needs to be developed to achieve this goal. This article looks at the relevant studies in the literature using content analysis. By adopting a qualitative methodology, the article collected and assessed measurements of tourism’s carbon emissions and examined the effects of implementing a low-carbon tourism programme. Some of the low-carbon strategies were listed by going through the entire implementation process of low-carbon tourism as an alternative form of tourism development. The discussion also focuses on how Covid-19 can influence low-carbon tourism development. A blueprint for a low-carbon recovery proposed by the Organisation for Economic Co-operation and Development (OECD) is also presented at the end of the paper. The results of this study can be used as a basis for policy development and further research on low-carbon tourism in industry sub-sectors worldwide.